Fish Allergy Around the World—Precise Diagnosis to Facilitate Patient Management - Kalic, Tanja; Radauer, Christian; Lopata, Andreas L.; Breiteneder, Heimo; Hafner, Christine (Frontiers in Allergy, 2021)
The accurate and precise diagnosis of IgE-mediated fish allergy is one of the biggest challenges in allergy diagnostics. A wide range of fish species that belong to evolutionary distant classes are consumed globally. Moreover, each fish species may contain multiple isoforms of a given allergen that often differ in their allergenicity. Recent studies indicated that the cross-reactivity between different fish species is limited in some cases and depends on the evolutionary conservation of the involved allergens. Fish allergens belong to several protein families with different levels of stability to food processing. Additionally, different preparation methods may contribute to specific sensitization patterns to specific fish species and allergens in different geographic regions. Here, we review the challenges and opportunities for improved diagnostic approaches to fish allergy. Current diagnostic shortcomings include the absence of important region-specific fish species in commercial in vitro and in vivo tests as well as the lack of their standardization as has been recently demonstrated for skin prick test solutions. These diagnostic shortcomings may compromise patients’ safety by missing some of the relevant species and yielding false negative test results. In contrast, the avoidance of all fish as a common management approach is usually not necessary as many patients may be only sensitized to specific species and allergens. Although food challenges remain the gold standard, other diagnostic approaches are investigated such as the basophil activation test. In the context of molecular allergy diagnosis, we discuss the usefulness of single allergens and raw and heated fish extracts. Recent developments such as allergen microarrays offer the possibility to simultaneously quantify serum IgE specific to multiple allergens and allergen sources. Such multiplex platforms may be used in the future to design diagnostic allergen panels covering evolutionary distant fish species and allergens relevant for particular geographic regions.